PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP WAKTU TUNGGU PELAYANAN OBAT DI INSTALASI FARMASI RS EMC TANGERANG - Juhaeri; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2023)
The quality of an institution can be seen from the performance of employees who have high motivation and work discipline. It can be seen that this study aims to find out the effect of motivation, work discipline, and work motivation and discipline on waiting time for drug service at the Pharmacy Installation in EMC Tangerang. The research method used in this research was quantitative research using questionnaires as an instrument. The distribution of questionnaires in the form of a Google Form was given to 44 employees who were the research samples. After distributing the questionnaires, the data were processed using SPSS version 27. The results of the validation and reliability tests showed that the questionnaires were feasible to use, because the validity test was rcount>rtable while the Cronbach's Alpha Standardization was higher than 0.61 for the reliability value. The results of the hypothesis show the value of 4.072 (X1) and 4.951 (X2) were higher than 2.018. The results of the F-test regarding the effect of motivation and work discipline on waiting time for drug services also showed a value of Fcount > Ftable (12.169> 3.230). Therefore, Ha1, Ha2 and Ha3 have an influence on variable Y so that Ha is accepted. All in all, staff at the installation of EMC Tanggerang hospital with the motivation and work discipline for them improve the performance of waiting time for drug services. However, R-square (determination) was 0,342, so it means that motivation (X1) and work discipline (X2) influenced to the waiting time for drug services (Y) which was 34,2%, and 71,7% was influenced by other factors that were not done in this research.